2023
DOI: 10.5144/0256-4947.2023.143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-pharmaceutical interventions on circulating respiratory viruses during the COVID-19 pandemic in Turkey

Füsun Kırca,
Sibel Aydoğan,
Aysegul Gozalan
et al.

Abstract: BACKGROUND: Non-pharmaceutical interventions (NPIs) applied to limit the SARS-CoV-2 pandemic also affect the circulation and seasonal characteristics of other respiratory viruses. OBJECTIVES: Assess the impact of NPIs on the spread and seasonal characteristics of non-SARS-CoV-2 respiratory viruses and examine viral respiratory co-infections. DESIGN: Retrospective cohort SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The COVID-19 pandemic affected the prevalence, seasonality, and incidence of seasonal respiratory viral infections, which also had an impact on the epidemiology of coinfections [ 35 ]. At the beginning of the pandemic, strict anti-epidemic measures were implemented that resulted in a low rate of reported coinfections, even in countries with a high prevalence of SARS-CoV-2 [ 41 ]. Our study found a 7.8% co-infection rate in the winter quarter of 2020, which was higher than the value (6.9%) in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic affected the prevalence, seasonality, and incidence of seasonal respiratory viral infections, which also had an impact on the epidemiology of coinfections [ 35 ]. At the beginning of the pandemic, strict anti-epidemic measures were implemented that resulted in a low rate of reported coinfections, even in countries with a high prevalence of SARS-CoV-2 [ 41 ]. Our study found a 7.8% co-infection rate in the winter quarter of 2020, which was higher than the value (6.9%) in 2021.…”
Section: Discussionmentioning
confidence: 99%